Alternative bile drains - Rompani, Omar C.; Estefan, Alberto; Praderi, Raúl (Cirugía del Uruguay, 1979)
After analyzing the problems derived from biliary suture permeation and possible appearence of postoperatory fistula, peritoneal drainage stands out as fundamental and alternative drainages are useful, in this type of surgery. There follows a description of three different types of tubes which can be employed in this type of surgery: offered tubes, Burlui and alternative drainages.